2007
DOI: 10.1158/1078-0432.ccr-07-1042
|View full text |Cite
|
Sign up to set email alerts
|

High Promoter Methylation Levels of APC Predict Poor Prognosis in Sextant Biopsies from Prostate Cancer Patients

Abstract: Purpose: Prostate cancer is a highly prevalent malignancy and constitutes a major cause of cancer-related morbidity and mortality. Owing to the limitations of current clinical, serologic, and pathologic parameters in predicting disease progression, we sought to investigate the prognostic value of promoter methylation of a small panel of genes by quantitative methylation-specific PCR (QMSP) in prostate biopsies. Experimental Design: Promoter methylation levels of APC, CCND2, GSTP1, RARB2, and RASSF1A were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 21 publications
5
99
0
Order By: Relevance
“…4,5 To date, aberrant hypermethylation of CpG island-containing promoters has been identified at numerous loci in PCa, including GSTP1 and APC. [7][8][9][10][11] However, relatively limited studies have used the quantitative PSQ method to explore DNA hypermethylation status of various genes in PCa. 5,6 In the earlier studies using multiple genes by the PSQ method, it was demonstrated that both APC and GSTP1 methylation levels were significantly higher in PCa samples than in control samples.…”
Section: Figure 1 Methylation Level Of (A) Adenomatous Polyposis Colmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 To date, aberrant hypermethylation of CpG island-containing promoters has been identified at numerous loci in PCa, including GSTP1 and APC. [7][8][9][10][11] However, relatively limited studies have used the quantitative PSQ method to explore DNA hypermethylation status of various genes in PCa. 5,6 In the earlier studies using multiple genes by the PSQ method, it was demonstrated that both APC and GSTP1 methylation levels were significantly higher in PCa samples than in control samples.…”
Section: Figure 1 Methylation Level Of (A) Adenomatous Polyposis Colmentioning
confidence: 99%
“…7,8,10,11 Although it is typically relatively high in PCa and low in BPH, the reported strength of the association varies widely between studies. 7,8,10,11 As previously mentioned, the inconsistency in methylation results for these genes may be due to differences in detection methods, regions of interest, and/or tissue types. In the present study, the combination of APC and GSTP1 methylation by a quantitative method yielded a sensitivity of 92.8% while maintaining a specificity of 100% for the discrimination of PCa samples from benign prostate samples.…”
Section: Figure 1 Methylation Level Of (A) Adenomatous Polyposis Colmentioning
confidence: 99%
See 1 more Smart Citation
“…Six could not provide data on the methylation among fluid samples (urine and blood), and 33-38 15 of the 29 articles using tissues had no raw data (the specific numbers of cases and controls with methylation were unclear, which made it difficult to calculate the data required for sensibility and specificity) or studied other factors such as the TMPRSS2 gene and urothelial carcinomas. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Finally, 19 studies met the inclusion criteria and were included. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Among these 19 studies, 5 involved body fluid (blood, urine and so on) [11][12][13][14][15] and the remaining 14 articles involved sample tissues.…”
Section: Characteristicsmentioning
confidence: 99%
“…[7][8][9] In prostate cancer, hypermethylation of several genes has been associated with tumor aggressiveness in terms of clinical-pathological characteristics, biochemical recurrence, and/or mortality from prostate cancer. [10][11][12][13][14][15][16] Global hypomethylation, which may cause reactivation of the transcription of oncogenes and transposable elements and increases chromosomal instability and loss of imprinting, 17,18 has been less extensively investigated. We have recently conducted a systematic review of studies on prostatic tumor global hypomethylation and prostate cancer progression: 19 although studies were heterogeneous and mostly based on a limited sample size, global hypomethylation was reported to be associated with high Gleason score, advanced tumor stage, high pre-operative PSA, and presence of metastasis.…”
Section: Introductionmentioning
confidence: 99%